Experimental Investigation of Temperature Polarization near Membrane Surface During Air Gap Membrane Distillation Processes - Lianqi Jing; Jiaqi Sun; Yaoling Zhang; Jiaming Chen; Fei Guo (Membranes, 2025)
Temperature polarization is a critical factor influencing the performance of membrane distillation. The presence of temperature polarization causes the temperature of the fluid near the membrane surface to be different from that in the bulk region, reducing the effective temperature difference across the membrane and thus diminishing the transmembrane mass transfer driving force. This study investigates the monitoring of temperature polarization and its effects on the transmembrane mass transfer performance in a typical air gap membrane distillation system. A set of thermocouples within a feed module were employed to monitor and capture the development of the temperature polarization profile. The test results reveal that temperature polarization reduces the effective temperature difference across the membrane, leading to a certain difference between the theoretical estimation and experimental values of the mass transfer coefficient across the porous membrane. To address this issue, the temperature polarization factor was further analyzed as a metric to quantify the impact of temperature polarization on the transmembrane flux in membrane distillation, with a detailed discussion of its range and implications.